Elemental imaging of trace elements in bone samples using micro and nano-X-ray fluorescence spectrometry. (July 2019) - Streli, C.; Rauwolf, M.; Turyanskaya, A.; Ingerle, D.; Wobrauschek, P.
Abstract: Our group employs micro- and nano-X-ray fluorescence spectrometry (XRF) for the investigation of bone tissue. The manuscript presents the results of 3 various projects, in which spatial distribution of trace elements in bone samples was studied. The first study investigated the distribution of the elemental constituents of Mg-based implants at various stages of the degradation process in surrounding bone tissue with a focus on magnesium (Mg) and yttrium (Y). The analysis was performed in laboratory of Atominstitut using a special micro-XRF spectrometer for light element detection. The second study is devoted to the spatial distribution of Zn in high-grade sclerosing osteosarcoma mapped by confocal synchrotron radiation induced micro-XRF. Tumor zinc levels were compared with adjacent normal tissue. For discrimination between healthy and diseased bone quantitative backscattered electron imaging was used. The third experiment demonstrates the performance of synchrotron radiation induced nano-XRF with beam size of about 500 nm for bone tissue investigation. Special emphasis is set to advantages of micro- and nano-XRF in bone analysis as well as overcoming possible limitations. Highlights: Micro-XRF was successfully applied to determine the element distribution in bone samples. A laboratory micro-XRF spectrometer was used to measure the Mg and Y distribution in bones after implantation of Mg-based bioresorbable implants. Synchrotron radiation induced confocal micro-XRF was successfully applied to determine the spatial distribution of Zn in osteosarcoma. Tumor zinc levels were compared with adjacent normal tissue and found to be higher. Synchrotron radiation induced nano-XRF with resolution of about 500 nm was used for bone tissue investigation with a high spatial resolution.